Search for active lava flows with VIRTIS on Venus Express. Issue 5 (27th May 2017) - Mueller, N. T.; Smrekar, S.; Helbert, J.; Stofan, E.; Piccioni, G.; Drossart, P.
Abstract: The Visible Infrared Thermal Imaging Spectrometer (VIRTIS) instrument on Venus Express observed thermal emission from the surface of Venus at 1 μm wavelength and thus would have detected sufficiently bright incandescent lava flows. No eruptions were detected in the observations between April 2006 and October 2008, covering an area equivalent to 7 times the planets surface on separate days. Models of the cooling of lava flows on Earth are adapted to Venus ambient conditions to predict thermal emission based on effusion rate. Taking into account the blurring of surface thermal emission by the atmosphere, the VIRTIS images would detect eruptions with effusion rates above 500 to 1000 m 3 /s. On Earth such eruptions occur but are rare. Based on an eruption rate and duration distribution fitted to historical data of three terrestrial volcanos, we estimate that only a few percent of all eruptions are detectable. With these assumptions the VIRTIS data can constrain the rate of effusive volcanism on Venus to be less than about 300 km 3 /yr, at least an order of magnitude higher than existing constraints. There remains a large uncertainty because of unknown properties of lava flows on Venus. Resolving flows in radar imaging and their thickness in altimetry might help to better constrain these properties. While VIRTIS data do not represent a significant constraint on volcanism, an optimized instrument with a 20 times better signal‐to‐noise ratio would likely be able to detect effusion rates on the order of 50 m 3 /s. Plain Language Summary: Venus has a thick, cloudy atmosphere that shields its surface from imaging and asteroid impacts. We know from radar imaging that there are many volcanos on Venus, but we do not know how active they are. The spacecraft Venus Express observed the infrared radiation of the hot surface of Venus through the global cloud layer. If there had been an active lava flow, the even higher surface temperature might have been detected in these data. We did not see anything in the data that clearly must have been caused by an active volcanic eruption. We show that only eruptions that produce a comparatively large volume of lava per second would be clearly visible. On Earth such eruptions occur but only a few per thousand years. It is possible that Venus has more volcanic eruptions than Earth, but not so many that we could have expected to find one in our data. We will need better observations to see more typical eruptions and more images to have a good chance of directly observing an eruption on Venus. Key Points: A search of VIRTIS data resulted in no detection of thermal emission of active lava flows on Venus A thermal and atmospheric model estimates size and eruption rate of detectable active lava flows Plausible assumptions on eruption volume and duration result in an upper bound of volcanic activity